Impact of Indirect Tax to the Economic Growth of Nepal - Sapkota, Tika Prasad (Journal of Business and Social Sciences, 2024)
This study looks at the structure and trends of indirect taxation in Nepal as well as how much indirect taxation contributes to the country's GDP. The economic growth is measure by GDP. The purpose of the study is determining the impact of value added tax, custom and excise duties on economic growth in Nepal. This study is based on secondary data that was released by the Nepal government between the fiscal years 2002/03 and 2022/2023. The research has embraced the casual comparative approach of analysis. It uses correlation, regression and coefficient of determination for examine the impact of VAT, Custom duty and excise duty to GDP. Over the course of the investigation, the indirect taxes percentage contribution to GDP varies between 6.60 and 14.96. Compared to previous years, the percentage contribution reduced in 2019/20 and 2022/23 but continued rise with the fluctuation pattern until 2021/22. The study concludes that there is positive relationship between different types of indirect tax and the economic growth. However, indirect tax revenue positively impacts to GDP over the study period.